IMPROVING STUDENTS' VOCABULARY MASTERY USING OUTDOOR ACTIVITIES (AN ACTION RESEARCH AT SIXTH YEAR OF SD NEGERI 2 SURU GEYER GROBOGAN IN 2009 / 2010 ACADEMIC YEAR) - WIDAYANTO, YUDHI (2010)
The general objective of this research is to improve the students' vocabulary mastery. While the specific objectives of this research are to describe the teaching of vocabulary using outdoor activities in SD Negeri 2 Suru, and to know whether the outdoor activities can improve the students' vocabulary or not. In achieving the objectives of the research, the researcher uses Classroom Action Research (CAR). Each cycle of the action consists of four steps: planning, implementing, observing, and reflecting. The research was held in SD Negeri 2 Suru Geyer Grobogan that consists of 39 students. In analyzing the data the researcher uses both qualitative and quantitative analysis taken from observation, document, test, and interview. There are two cycles in this action research in which each cycle is conducted in two meetings. After analyzing the data, the writer describes the result of the research in which the mean score of pre-test is 66.79, in post-test 1 is 75.26, and in post-test 2 is 83.85. The results both of pre-test and post-test indicate that the students have a significant improvement in vocabulary mastery. Through Outdoor Activities, the students are motivated in learning vocabulary. The students become more active and creative in teaching-learning. They are also very enthusiastic, braver and more confident in practicing English. Thus, it can be said that the teaching vocabulary using Outdoor Activities is successful to improve students' vocabulary mastery in SD Negeri 2 Suru Geyer Grobogan.